Individual, employment and psychosocial factors influencing walking to work: Implications for intervention design. - Emma J Adams; Dale W Esliger; Ian M Taylor; Lauren B Sherar (PLoS ONE, 2017)
Promoting walking for the journey to and from work (commuter walking) is a potential strategy for increasing physical activity. Understanding the factors influencing commuter walking is important for identifying target groups and designing effective interventions. This study aimed to examine individual, employment-related and psychosocial factors associated with commuter walking and to discuss the implications for targeting and future design of interventions.1,544 employees completed a baseline survey as part of the 'Walking Works' intervention project (33.4% male; 36.3% aged <30 years). Multivariate logistic regression was used to examine the associations of individual (age, ethnic group, educational qualifications, number of children <16 and car ownership), employment-related (distance lived from work, free car parking at work, working hours, working pattern and occupation) and psychosocial factors (perceived behavioural control, intention, social norms and social support from work colleagues) with commuter walking.Almost half of respondents (n = 587, 49%) were classified as commuter walkers. Those who were aged <30 years, did not have a car, had no free car parking at work, were confident of including some walking or intended to walk to or from work on a regular basis, and had support from colleagues for walking were more likely to be commuter walkers. Those who perceived they lived too far away from work to walk, thought walking was less convenient than using a car for commuting, did not have time to walk, needed a car for work or had always travelled the same way were less likely to be commuter walkers.A number of individual, employment-related and psychosocial factors were associated with commuter walking. Target groups for interventions to promote walking to and from work may include those in older age groups and those who own or have access to a car. Multi-level interventions targeting individual level behaviour change, social support within the workplace and organisational level travel policies may be required in order to promote commuter walking.